Analysis of the implementation of the "Man and the Biosphere" programme in the biosphere reserves of Andalusia - Castaño-Quintero, Paula Andrea; Gil-Cerezo, María Victoria; Galán Soldevilla, Carmen; Domínguez-Vilches, Eugenio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
The Spanish Committee for the Man and the Biosphere (MaB) Programme runs a programme that monitors the Spanish Network of Biosphere Reserves. The monitoring programme features a system of indicators enabling the degree of implementation and the territorial integration of the Biosphere Reserves (BRs) located on Spanish territory to be studied. This paper sets out a statistical analysis based on the results of the degree of implementation for the BRs of Andalusia (Spain) obtained for the period 2008-2014. The analysis allows identification of the indicators that have had the most influence on the degree of implementation in the Andalusian BRs, as well as the factors that may be strengthened in order to enhance the degree of implementation. The effectiveness of the indicator system will be improvement if additional work is done to redefine those conceptual aspects that tend to generate discrepancies in the interpretation of compliance with the requirements of the variables. To improve the management of the Andalusian BRs, complementary studies to allow the evaluation of the impact of the initiatives related to the implementation of the MaB Program should be carried out.